2020
DOI: 10.1186/s12866-020-01847-y
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal inflammatory cytokines, barrier proteins and microbiome-metabolome responses to early supplementary feeding of Bamei suckling piglets

Abstract: Background: Dietary intervention has been reported to improve intestinal health. The intestinal microbiota of newborn animals plays a fundamental role in the development of intestinal function and the innate immune system. However, little is currently known about dietary interventions in the gut microbiota and barrier function of livestock, especially suckling Bamei piglets. To this end, we studied the effect of early dietary supplementation on intestinal bacterial communities and intestinal barrier function i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…As a “second genome” for modulating the health phenotype of the superorganism host, gut microbiota are closely associated with host nutrition, metabolism, and immunity ( Jia et al, 2008 ; Jin et al, 2020 ). It has been reported that an HFD disrupts gut microbiota in two ways: via diminishing the levels of gut barrier-protecting probiotics such as Bifidobacteria and promoting the growth of endotoxin producers.…”
Section: Discussionmentioning
confidence: 99%
“…As a “second genome” for modulating the health phenotype of the superorganism host, gut microbiota are closely associated with host nutrition, metabolism, and immunity ( Jia et al, 2008 ; Jin et al, 2020 ). It has been reported that an HFD disrupts gut microbiota in two ways: via diminishing the levels of gut barrier-protecting probiotics such as Bifidobacteria and promoting the growth of endotoxin producers.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) reported that the greater nutritional function of the microbiota in the jejunum is more related to the energetic metabolism and fiber degradation. In addition to digestive functions, the intestinal microbiota produce bioactive compounds that can affect the jejunal immune system, barrier function, and cell proliferation ( Jin et al., 2020 ). According to Zhao et al.…”
Section: Composition Of Intestinal Microbiotamentioning
confidence: 99%
“…Previous studies used milk as a substitute for sow milk and the findings showed that it improved intestinal function and upregulated expression of tight junction proteins. For example, Jin et al ( 42 ) reported that milk supplementation changes mRNA expression levels of ZO-1, Occludin , and Claudin-1 . The synthetic milk may potentially harbor specific growth factors which improved expression of tight junction proteins ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jin et al ( 42 ) reported that milk supplementation changes mRNA expression levels of ZO-1, Occludin , and Claudin-1 . The synthetic milk may potentially harbor specific growth factors which improved expression of tight junction proteins ( 42 ). Moreover, Lactobacillus may have upregulated gene expression of tight junction proteins ( 43 ).…”
Section: Discussionmentioning
confidence: 99%